The multifunctional buzzer watch: a solution for deaf people - Zaidee, Alya Batrisyia; Zaini, Nur Shafiqa Aziqa; Jeffridin, Nur Ani Syafiqah; Samsul, Nurul Ain Sakinah; Herman, Putri Nur Jannah; Mohamed, Munirah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
People who are deaf frequently have difficulty getting key alerts and notifications that are critical for their safety and convenience in everyday life. The current timekeeping tools and notification systems fail to meet their accessibility requirements, making it necessary to develop innovative solutions. The Multifunctional Buzzer Watch has been designed to address this gap by offering timekeeping functionality and advanced sound detection capabilities. The watch alerts wearers through wrist vibrations to important environmental sounds, enabling deaf people to be more alert and independent. It aims to promote situational awareness by combining modern design, sensor technology, and practical functionality, empowering deaf individuals to navigate daily activities with greater confidence and safety. The unique feature of the watch is that it has both a sensor and a buzzer. The sensor can detect any sound nearby, such as a knocking door or a whistling kettle, and will signal the buzzer. The findings affirm the practicality and usefulness of the Multifunctional Buzzer Watch as a valuable watch for enhancing the quality of life and inclusion of deaf people in society.